1999
DOI: 10.1007/s001340050815
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic performance and customization of the SAPS II: results of a multicenter Austrian study

Abstract: SAPS II was not well calibrated when applied to all patients. However, it performed well for patients with cardiovascular diseases as the primary reason for admission and may thus be applied to these patients. Standardized mortality ratios that are calculated from scoring systems without known calibration must be viewed with skepticism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
4
7

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 11 publications
2
49
4
7
Order By: Relevance
“…Several authors indeed showed that if the SAPS II model has a good discriminative power, its calibration is poor when applied to an independent case mix [8,17]. However, although it seemed to perform adequately in our patients' sample, we found, like other authors, that the SAPS II predictive model tended to overestimate the hospital mortality [8,17,18]. The present study has potential limitations.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Several authors indeed showed that if the SAPS II model has a good discriminative power, its calibration is poor when applied to an independent case mix [8,17]. However, although it seemed to perform adequately in our patients' sample, we found, like other authors, that the SAPS II predictive model tended to overestimate the hospital mortality [8,17,18]. The present study has potential limitations.…”
Section: Discussioncontrasting
confidence: 66%
“…Although more recent severity scores versions were developed in the nineties [2][3][4], the APACHE II remains, to date, the most widely used scoring system for ICUs assessment and for clinical trials conducted in the field of critical care medicine. Nevertheless, several studies showed a deterioration of both APACHE II and SAPS II scores performances [5][6][7][8]. The recently published SAPS 3 admission score [9] is a model built to predict hospital mortality from admission data (recorded within ±1 h).…”
Section: Introductionmentioning
confidence: 99%
“…There are many potential causes for suboptimal calibration. 33 It is infl uenced especially by case mix. …”
Section: Calibrationmentioning
confidence: 99%
“…Our results demonstrate much higher values on admission, for maxi mum score, and also in mortality, prob ably because the patients were suffering from CS complicating AMI. Mentnitz and colleagues [29] demonstrated that the SAPS II score was of good assistance in mortality evaluation in cardiac patients.…”
Section: Scoring In Cardiogenic Shockmentioning
confidence: 99%